Recent advancements in nanozyme hydrogel based system for enhanced sensing applications - Simran Makkar; Nikita Sarawagi; Nitesh Priyadarshi; Sunaina Kaul; Palakjot Kour Sodhi; Ajay Kumar Srivastava; Nitin Kumar Singhal (Biosensors and Bioelectronics: X)
In recent years, combining hydrogels with nanozymes has shown promise as a platform for sensing applications. Nanozymes are simple, affordable, and stable alternatives that use enzyme-like capabilities. Conversely, hydrogels provide hydrated, biocompatible environments, which enhance the stability and activity of nanozymes. The most recent advancements in nanozyme-hydrogel hybrid sensing systems are examined in this study, with a focus on their enzymatic activities—peroxidase and oxidase mimetics—and how they can be used to detect a variety of analytes, such as glucose, pesticide, and many more.In addition to simulating the biological environment, the synergistic combination of hydrogels and nanozyme improves the biosensor's sensitivity, specificity, and fast reaction times. These hybrid systems also provide an extensible framework for integrating multiple sensory modalities into a single functional device. This review highlights the groundbreaking potential and uses of hydrogel sensors based on nanozymes in environmental and medical diagnostics and potential future developments.